Tomato SlBES1.8 Influences Leaf Morphogenesis by Mediating Gibberellin Metabolism and Signaling. (8th February 2022) - Su, Deding; Xiang, Wei; Liang, Qin; Wen, Ling; Shi, Yuan; Song, Bangqian; Liu, Yudong; Xian, Zhiqiang; Li, Zhengguo
Abstract: Leaf morphogenetic activity determines its shape diversity. However, our knowledge of the regulatory mechanism in maintaining leaf morphogenetic capacity is still limited. In tomato, gibberellin (GA) negatively regulates leaf complexity by shortening the morphogenetic window. We here report a tomato BRI1-EMS-suppressor 1 transcription factor, SlBES1.8, that promoted the simplification of leaf pattern in a similar manner as GA functions. OE- SlBES1.8 plants exhibited reduced sensibility to exogenous GA3 treatment whereas showed increased sensibility to the application of GA biosynthesis inhibitor, paclobutrazol. In line with the phenotypic observation, the endogenous bioactive GA contents were increased in OE- SlBES1.8 lines, which certainly promoted the degradation of the GA signaling negative regulator, SlDELLA. Moreover, transcriptomic analysis uncovered a set of overlapping genomic targets of SlBES1.8 and GA, and most of them were regulated in the same way. Expression studies showed the repression of SlBES1.8 to the transcriptions of two GA-deactivated genes, SlGA2ox2 and SlGA2ox6, and one GA receptor, SlGID1b-1 . Further experiments confirmed the direct regulation of SlBES1.8 to their promoters. On the other hand, SlDELLA physically interacted with SlBES1.8 and further inhibited its transcriptional regulation activity by abolishing SlBES1.8–DNA binding. Conclusively, by mediating GA deactivation and signaling, SlBES1.8 greatly influenced tomato leaf morphogenesis.